Penerapan Pembelajaran Daring Dragonlearn pada Era Pandemic Covid-19(Studi Kasus di MI Ma’had Islam Kopeng) - Aniq Amalia; Siti Fatonah (ISEJ : Indonesian Science Education Journal, 2020)
The purpose of this study was to determine the optimization of mathematics learning during the New Normal due to the impact of the Covid-19 pandemic. In addition, to find out the implementation process, advantages, and obstacles of online learning with Dragonlearn. This type of research uses a qualitative approach. Data collection techniques using the method of observation, interviews, and documentation. The data analysis stage includes: data reduction, data presentation, and drawing conclusions. The results showed that: 1) optimizing mathematics learning during the New Normal period at MI Ma'had Islam Kopeng using the home visit learning method as an alternative to learning. Before using the home visit learning method, the school conducted online or online learning. However, this method cannot run smoothly and cannot be enjoyed by some students, especially those whose home addresses are remote and do not have supporting facilities to obtain material through online learning. 2) The process of implementing Dragonlearn Era New Normal online learning has been going well, by carrying out careful planning students can carry out learning smoothly so that teachers can evaluate through the available statistics page. 3) The advantage of using dragonlearn is that students are more active and more confident in asking questions, they can access it anytime and anywhere. However, learning like this has obstacles that lie in the network. This learning also has disadvantages, namely that there are convoluted types of questions and the learning cannot be face-to-face so that the teacher cannot convey the material optimally.